PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI EDUKATIF KEARIFAN LOKAL JAWA BARAT PADA MATERI KERAGAMAN BUDAYA UNTUK MENINGKATKAN LITERASI BUDAYA SISWA KELAS IV SEKOLAH DASAR - Sania Putri Cantika; Yona Wahyuningsih; Agil Nanggala (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Cultural literacy among elementary school students still needs to be strengthened, as the teaching of cultural diversity in the Natural and Social Sciences (IPAS) subject is generally still dominated by verbal delivery of content and has not been supported by interactive learning media that are contextual to local wisdom. This study aims to develop the Monopoli Edukatif Kearifan Lokal Jawa Barat learning medium, and to examine its feasibility, user responses, and effectiveness in improving the cultural literacy of fourth-grade elementary school students. The study used the Design and Development (D&D) Type 1 method by Richey and Klein with a One-Group Pretest–Posttest design. Participants consisted of 24 fourth-grade students and one classroom teacher at SDN Sukamenak 03, while the feasibility of the medium was assessed by a material expert, a media expert, and a language expert. Qualitative data were analyzed using the Miles and Huberman interactive model, and quantitative data were analyzed using the Wilcoxon Signed Rank Test and N-Gain calculation. The results showed that the medium obtained an average validation percentage of 93.53%, categorized as very feasible. Teacher and student responses were also highly positive, at 100% and 94.9% respectively. The Wilcoxon test showed a significant difference between pretest and posttest scores (Asymp. Sig. (2-tailed) = 0.000), and the N-Gain value of 0.7046 fell into the high category. This improvement was reflected across all cultural literacy indicators, namely cultural awareness, awareness of history and its impact, and tolerance. The Monopoli Edukatif Kearifan Lokal Jawa Barat medium is thus considered feasible, was very well received, and effectively improved the cultural literacy of fourth-grade elementary school students.